The Survey of 2013 Curriculum Implementation on Physical Education in the Elementary Schools of Bekasi City - Yusmawati Yusmawati; Aridhotul Haqiyah; Dani Nur Riyadi (JETL (Journal of Education, Teaching and Learning), 2020)
The purpose of this study was to find out the implementation of the 2013 Curriculum in Bekasi Elementary Schools. The method used in this study is the survey method. The sample in this study was a physical education teacher who taught at the Bekasi Elementary School amount of 30 people. The instrument used by the questionnaire of teaching indicators which include: (a) preparation factors, (b) application factors, and (c) evaluation factors. Data analysis technique were descriptive statistics by using the SPSS Version 23 program. The result showed that the 2013 curriculum implementation of physical education teachers is viewed from 3 factors which are as follows: (1) Preparation shows the very high result as many as 32.6%, while as many as 14.8% answered very low, 7.3% answered low, 16.3% answered moderate, and 29.1% answered high, (2) Application shows the high result as many as 35.1%, while as many as 16.4% answered very low, 14.1% answered low, 12.6% answered moderate, and 21.9% answered very high, (3) Evaluation shows the high result as many as 41.9%, while 7.6% answered very low, 7.6% answered low, 11% answered moderate, and 31.9% answered very high. So, the implementation of the 2013 curriculum in Physical Education subjects in Bekasi is already good in the preparation factor and needs improvement in application and the evaluation.